Politik Hukum Hak Cipta: Meletakkan Kepentingan Nasional Untuk Tujuan Global - Budi Agus Riswandi (Jurnal Hukum IUS QUIA IUSTUM, 2004)
The logical consequences for Indonesia when it takes ratification on GAIT/WTO agreement in which it contains TRIPS agreement cause the disharmonization in the national law for intellectual copyright. One oflaw on copyright is the existence oflaw on copyright viewed political law perspective is still dominated byforeign interest. Whereas ideally, the law created nationally tends to bring the national interest. The national interest must betranslated, in the frame of gaining its objective.